Radicalization - McDonald, Kevin (Polity, 2018)
From Paris to San Bernardino, Barcelona to Manchester, home-grown terrorism is among the most urgent challenges confronting Western nations. Attempts to understand jihadism have typically treated it as a form of political violence or religious conflict. However, the closer we get to the actual people involved in radicalization, the more problematic these explanations become. In this fascinating book, Kevin McDonald shows that the term radicalization unifies what are in fact very different experiences. These new violent actors, whether they travelled to Syria or killed at home, range from former drug dealers and gang members to students and professionals, mothers with young children and schoolgirls. This innovative book sets out to explore radicalization not as something done to people but as something produced by active participants, attempting to make sense of themselves and their world. In doing so, McDonald offers powerful portraits of the immersive worlds of social media so fundamental to present-day radicalization.Radicalization offers a bold new way of understanding the contemporary allure of jihad and, in the process, important directions in responding to it.